41. KNOWLEDGE OF THE EARLY WARNING SIGNS OF STROKE AMONG CAREGIVERS IN BINH HOA COMMUNE, GIAO THUY DISTRICT, NAM DINH PROVINCE (Vietnam Journal of Community Medicine, 2025)
Objective: This study was conducted to assess the knowledge of early signs of stroke in caregivers in Binh Hoa commune, Giao Thuy district, Nam Dinh province.Methods: cross-sectional study on 110 caregivers participating in the survey.Results: The study showed that the average age was 37.32 ± 15.88. The proportion of women was 50.9%. In terms of education level, 42.8% had an undergraduated and higher, 45.4% had completed primary, secondary and high school, and 11.8% had never attended school. The common occupation was the labor group, accounting for 64.5%. In terms of work, 60.9% worked full-time, 13.6% part-time and 25.4% did not work. 50.9% of the study subjects recognized the early signs of stroke (FAST); 44.5% of the study subjects recognized the early signs of stroke (BEFAST).Conclusion: The study showed that 50.9% and 44.5% of caregivers met the requirements for knowledge of recognizing FAST and BEFAST signs. It is necessary to promote propaganda, consultation and organize training courses to equip caregivers with necessary knowledge, help caregivers detect stroke early and support proper treatment, contributing to reducing the rate of complications and mortality.
Keywords: knowledge; stroke; caregivers.